ECONOMIC DIVERSITY AND MARKETING PATTERN OF VEGETABLE FARM BUSINESS IN DISTRICT OF MEDAN MARELAN - Sri Endang Rahayu; Mailina Harahap (AGRIUM: Jurnal Ilmu Pertanian, 2015)
Economic development is increasingly pushing human necessities of life so that agricultural development is directed to agribusiness activities. As the Government of the city of Medan set area agribusiness and one of them is Medan Marelan flagship commodities with vegetable soup. The study aimed to find out how the economic diversity  and marketing pattern of vegetable farmer. Sample research are farmers vegetable soup in Medan Marelan taken in purposive sampling. Note the average age of respondents 57 years of age, educational level or equivalent to 8 years class II middle school (Junior High School), the number of members of the family of 4 people, the experience of the farmer of 12.8 years, extensive farm farmer 800 m2 as for the respondent's own tenure with 26 respondents and land annual rent 14 respondents.Types of vegetables planted are spinach, Kale, mustard greens, sweet Pakchoy, Kai-and long beans. Financially is known to the average farmer cost IDR 4,957,750 average total acceptance of farmer respondents from all commodity vegetable is IDR 13,472,102 and the average profit earned farmers at one time production of vegetables is IDR 8,514,352 Vegetable marketing agencies in the know:a). Farmers directly as traders retailer – Consumer, b).Farmers – Traders collecting sub – Central Market – Traders Retailer-consumer, c).Farmers – Traders collecting sub – Super market-consumerKeyword: vegetable farmer, economic diversity, the pattern of marketing